THE DISTINCTIVE APPROACH TO RATIONAL AND TRANSMITTED PROOFS IN MATURIDI THEOLOGY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the distinctive approach of Maturidi theology to rational (aqlī) and transmitted (naqlī) proofs. The study begins by defining the key terms dalil (proof), naqlī dalil, and aqlī dalil and then comparatively situates the Maturidi school within the broader typology of methodological approaches to the knowledge of truth. The article traces the five-part classification of epistemological orientations formulated by Imam al-Ghazali, the three guiding principles of Ahl al-Sunna’s balanced method, and the specific position of the Maturidiyya as a school that grants wider scope to reason than the Ash’ariyya while maintaining the primacy of transmitted evidence over the Mu’tazila. The conclusion argues that the Maturidi synthesis of reason and revelation constitutes one of the most intellectually rigorous and practically relevant achievements of classical Islamic theology.
Keywords: Maturidiyya; rational proof (aqlī dalil); transmitted proof (naqlī dalil); kalam; Ash’ariyya; Mu’tazila